Effect of SiO2 solid loading and sintering temperatures on the physical properties of SiO2-NiO foam - Muda, Rizamarhaiza; Azmi, Mohd Azham; Mahzan, Shahruddin; Elwalwal, Hatem Mostafa; Ahmad, Sufizar; Taib, H. (Trans Tech Publications, 2018)
Porous ceramic is a type of material that has highly open and partially interconnected pores. It has a wide range of applications which include catalyst support, electrical conductivity, refractory insulation of furnaces, filtration, adsorption, and separation. There are many conventional methods for producing silica foam including direct forming, steam heating, freeze casting and the polymeric sponge method which is also known as the replication method. In this study, SiO2-NiO foam was fabricated using 25wt. %, 30wt % and 35wt.% of SiO2 and 5wt.% of NiO under different sintering temperatures (850˚C and 1050˚C) via replication method. The morphologies of SiO2-NiO foams were observed using Scanning Electron Microscopy (SEM) while the identification of the different phases of foam was analysed using X-Ray Diffraction (XRD). The XRD analysis indicated that there were only SiO2 and NiO present and no additional phases were detected after sintering. The effects of sintering temperature (850˚C, 1050˚C) and SiO2 solid loading on properties such as apparent porosity, bulk density and shrinkage were investigated. It was found that when the solid loading of SiO2 and sintering temperature increased, the density of SiO2-NiO foams increased in the range of 0.6373 g/cm3 to 0.8165 g/cm3 . On the other hand, the porosity percentage obtained increased from 78.51 % to 81.63 %. The density and porosity analyses showed that the density of foam increases when the porosity of SiO2-NiO foam decreases. However, the shrinkage after sintering ranged between 3.5081cm to 6.9975 cm at 850C˚ and 7.3618 cm to 8.3704 cm at 1050˚C respectively. Thus, this proves that SiO2-NiO foam can be successfully fabricated through the replication method.